2024
DOI: 10.3390/app14052182
|View full text |Cite
|
Sign up to set email alerts
|

Improved SE-ResNet Acoustic–Vibration Fusion for Rolling Bearing Composite Fault Diagnosis

Xiaojiao Gu,
Yang Tian,
Chi Li
et al.

Abstract: An enhanced fault diagnosis approach for rolling bearings with composite faults using an optimized Squeeze and Excitation ResNet (SE-ResNet) model is proposed. This method integrates grid search (GS), support vector regression (SVR), ensemble empirical mode decomposition (EEMD), and low-rank multimodal fusion (LMF) to effectively handle the signals of acoustic–vibration fusion. By combining these techniques, the aim is to improve the accuracy and reliability of rolling bearing fault diagnosis. Firstly, improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…CNNs excel in learning hierarchical representations, which are vital for distinguishing fault features from noise [24][25][26]. Studies have demonstrated that CNN-based models outperform traditional methods in both accuracy and robustness under varying noise conditions [27][28][29]. These models can capture complex patterns and interactions within the data that are often missed by traditional techniques.…”
Section: Introductionmentioning
confidence: 99%
“…CNNs excel in learning hierarchical representations, which are vital for distinguishing fault features from noise [24][25][26]. Studies have demonstrated that CNN-based models outperform traditional methods in both accuracy and robustness under varying noise conditions [27][28][29]. These models can capture complex patterns and interactions within the data that are often missed by traditional techniques.…”
Section: Introductionmentioning
confidence: 99%